Mapping the topology-localization phase diagram with quasiperiodic disorder using a programmable superconducting simulator - Xuegang Li; Huikai Xu; Junhua Wang; Ling-Zhi Tang; Dan-Wei Zhang; Chuhong Yang; Tang Su; Chenlu Wang; Zhenyu Mi; Weijie Sun; Xuehui Liang; Mo Chen; et al. (Physical Review Research)
We explore a topology-localization phase diagram by simulating a one-dimensional Su-Schrieffer-Heeger model with quasiperiodic disorder using a programmable superconducting simulator. We experimentally map out and identify various trivial and topological phases with extended, critical, and localized bulk states. We find that with increasing disorder strength, some extended states can be first replaced by localized states and then by critical states before the system finally becomes fully localized. The critical states exhibit typical features such as multifractality and self-similarity, which lead to surprisingly rich phases with different types of mobility edges and scaling behaviors on the phase boundaries. Our results shed light on the investigation of the topological and localization phenomena in condensed-matter physics.